Androgen deprivation causes selective deficits in the biomechanical leg muscle function of men during walking: a prospective case–control study. Issue 1 (2nd August 2016) - Cheung, Ada S.; Gray, Hans; Schache, Anthony G.; Hoermann, Rudolf; Lim Joon, Daryl; Zajac, Jeffrey D.; Pandy, Marcus G.; Grossmann, Mathis
Abstract: Background: Although muscle mass declines with testosterone deficiency in men, previous studies of muscle function have not demonstrated consistent deficits, likely due to relatively insensitive methodology. Our objective was to determine the effects of testosterone deprivation on the biomechanical function of individual lower‐limb muscles. Methods: We conducted a 12‐month prospective, observational case–control study of 34 men newly commencing androgen deprivation treatment (ADT) for prostate cancer and 29 age‐matched prostate cancer controls. Participants were assessed at 0, 6, and 12 months while walking in a biomechanics laboratory. We combined video‐based motion capture and ground reaction force data with computerized musculoskeletal modelling to assess the following primary outcomes: (i) peak joint torques at the hip, knee and ankle, and corresponding individual muscle forces; (ii) individual muscle contributions to acceleration of the body's centre of mass; and (iii) walking speed, stride length, and step width. A linear mixed model was used to compare mean differences between groups. Results: Compared with controls over 12 months, men receiving ADT had a mean reduction in total testosterone level from 14.1 to 0.4 nmol/L, and demonstrated more marked decreases in peak hip flexor torque by 14% [mean difference −0.11 N/kg (−0.19, −0.03), P = 0.01] and peak knee extensor torque by 16% [−0.11 N/kg (−0.20, −0.02), P = 0.02] of the initial mean value. Correspondingly, iliopsoas force decreased by 14% ( P = 0.006), and quadriceps force decreased by 11%, although this narrowly missed statistical significance ( P = 0.07). Soleus decreased contribution to forward acceleration of the body's centre of mass by 17% [mean difference −0.17 m/s 2 (−0.29, −0.05), P < 0.01]. No significant changes between groups were observed in other joint torques or individual muscle contributions to acceleration of the body. Step width increased by 18% [mean adjusted difference 1.4 cm (0.6, 27.4), P = 0.042] in the ADT group compared with controls, with no change in stride length or walking speed. Conclusions: Testosterone deprivation selectively decreases lower‐limb muscle function, predominantly affecting muscles that support body weight, accelerate the body forwards during walking, and mediate balance. Future exercise and pro‐myogenic interventional studies to mitigate ADT‐associated sarcopenia should target these deficits.